I'm guessing that's 35x^2 + 26x - 16 which factors to (5x - 2)(7x + 8)
25x + 35x + 9 is 60x + 9, which factors to 3(20x + 3)
5 * 7 * x * x * x
(5x - 7)(7x + 5)
35x + 115 = 360 35x = 360-115 35x = 245 x = 245/35 x = 7
(7x-3)(2x+5) 14x2 + 29x - 15, write 29x = 35x - 6x = 14x2 - 6x + 35x - 15 = (14x2 - 6x) + (35x - 15) = 2x(7x - 3) + 5(7x - 3) = (7x-3)(2x+5)
25x + 35x + 9 is 60x + 9, which factors to 3(20x + 3)
5x2
7(5x + 9y)
7(5x + 4y)
5 * 7 * x * x * x
The GCF is 5x3
(5x - 7)(7x + 5)
x^(3) - 12x^(2) + 35 x Factor out 'x' Hence x(x^(2) - 12x + 35) Factor the quadratic x(x - 5)(x - 7) Done!!!!!
35x
7(5x + 9y)
35x + 15x = 50x
5(x2 - 7x + 12) = 5(x - 3)(x - 4)